Implementasi Model Pembelajaran Problem Based Learning pada Pelajaran IPS Kelas VII di SMPN 37 Samarinda - Herlina Mbara; Muhamad Sopyan (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
The purpose of this study was to investigate how the Problem-Based Learning paradigm is used in social studies classes at SMPN 37 Samarinda and to determine the elements that facilitate and hinder its adoption. This study focuses on the use of problem-based learning to help students improve their communication, teamwork, and critical thinking skills. It is hoped that by understanding how Problem-Based Learning is applied in social studies education, this study will help teachers optimize more creative and successful teaching strategies and assist in the creation of learning tactics that are more in line with the needs of contemporary students. The application of the Problem-Based Learning paradigm in social studies classes at SMPN 37 Samarinda was examined in this study using qualitative methodology. Data collection techniques included recording, interviews, and observations. The findings of the study indicate that the use of the problem-based learning paradigm in SMP Negeri 37 Samarinda in teaching social studies effectively develops students' capacity for critical, imaginative, and cooperative thinking. Problem-based learning has succeeded in encouraging active student involvement through problem-based learning stages, supported by a curriculum that is adaptive to student needs, adequate resources, trained teachers, and a conducive learning environment, although it still faces obstacles such as limited time, resources, and student motivation.